Development and Validation of the Soft Skills Questionnaire for Nurses - Mona Aridi MS; Manal Ahmad MA; Wissam Ghach PhD; Samiha Charifeh MA; Nisreen Alwan PhD (SAGE Publishing, 2023)
Introduction Skills challenge has been given great attention for its impact on employees' performance. Various approaches have been put forward to design professional development programs that help in preparing nurses to work in the field and ongoing training programs to keep them up to each new method and technique at the interpersonal improvement level. Objective To develop and validate a questionnaire that tests the communication and management skills, emotional intelligence, and confidentiality of nurses in Lebanon. Methods The questionnaire, consisting of 25 statements, was generated and developed by experts in the field of nursing, soft skills, and questionnaire development. The items of the questionnaire were assessed using face, content, and construct validity and data validation was examined through psychometric properties at the final stage of the validation. Internal consistency and reliability were assessed through Cronbach alpha ( α ). Further analyses were carried out to decide on the number of factors to be extracted using Oblimin Rotation method. All statistical tests were performed using Statistical Package for the Social Sciences (SPSS 20.0). Results Nineteen items of the 25-item scale had an I-CVI of 1.00 and the remaining six items had an I-CVI of 0.87. The S-CVI/UA was 0.76 and the S-CVI/Ave was 0.97, which meant that the items were good for the underlying construct. For the psychometric measures, the results were quite accepted and satisfactory. The Kaiser-Meyer-Oklin measure of sampling adequacy and the significance for the Bartlett's test for the whole questionnaire were quite acceptable with 0.680 and 0.000, respectively. Furthermore, the Cronbach alpha ( α ) value was 0.824 indicating a high internal consistency between the items of the questionnaire. While obtaining exploratory factor analysis for each section, results showed that Oblimin Rotation method should be applied to the last section in which three items were eliminated to maintain a simple factor structure. Conclusion This study shows that the 25-item Soft Skills Questionnaire is a valid and reliable tool for evaluating the level of communication of nurses, their emotional intelligence, confidentiality, and management.